Response to “Prenatal Gentle Yoga as a Non-Pharmacological Strategy to Accelerate the Active Phase of the First Stage of Labor in Primigravida Women” - Indriana Widya Puspitasari; Heni Puji Wahyuningsih; Sujiyatini Sujiyatini (FORIKES, 2026)
Dear Editor,I would like to express my appreciation for the publication entitled “Prenatal Gentle Yoga Sebagai Strategi Nonfarmakologis untuk Mempercepat Kala I Fase Aktif Persalinan Primigravida (Prenatal Gentle Yoga as a Non-Pharmacological Strategy to Accelerate the Active Phase of the First Stage of Labor in Primigravida Women)” [1]. This study offers notable strengths, particularly its focus on primigravida women—a group that often encounters substantial physiological and psychological challenges during their first labor experience. The use of prenatal gentle yoga as a non-pharmacological intervention, integrating breathing exercises, pelvic muscle stretching, and relaxation techniques, appears to be effective in accelerating the active phase of labor. Moreover, the application of a post-test only control group experimental design enhances the methodological rigor in identifying a causal relationship between the intervention and the observed clinical outcomes.Nevertheless, several limitations merit consideration. The relatively small sample size (n = 40) restricts the generalizability of the findings to a broader population [2,3]. In addition, the study does not assess other important variables such as analgesia requirements, neonatal outcomes, and maternal satisfaction with the childbirth process, all of which are essential for a more comprehensive evaluation of the intervention’s effectiveness [4]. Physical activity outside the yoga sessions was also not objectively controlled, leaving room for potential confounding bias [5]. Furthermore, the qualitative data presented remain largely descriptive and informal, lacking a systematic approach such as in-depth interviews or thematic analysis.For future research, it would be beneficial to conduct similar studies with larger sample sizes and to adopt a mixed-methods approach in order to better capture the subjective experiences of mothers. Including additional outcome indicators—such as the duration of the second stage of labor, use of analgesia, and long-term postpartum recovery—would provide a more comprehensive understanding of the benefits of prenatal gentle yoga. Such improvements would strengthen the evidence base and support the integration of this intervention into community-based antenatal care practices.